High-throughput screening of solid-state catalysts for nerve agent degradation. Issue 45 (21st May 2018) - Palomba, Joseph M.; Credille, Cy V.; Kalaj, Mark; DeCoste, Jared B.; Peterson, Gregory W.; Tovar, Trenton M.; Cohen, Seth M.
Abstract : A high-throughput screening (HTS) method was devised to increase the rate of discovery and evaluation of nerve agent degradation catalysts. Abstract : A high-throughput screening (HTS) method was devised to increase the rate of discovery and evaluation of nerve agent degradation catalysts. Using this HTS method, >90 solid state materials, predominantly metal–organic frameworks (MOFs), were analyzed for their ability to hydrolyze the nerve agent simulant methyl paraoxon at two pH values (8.0 and 10.0).